VARIASI BAHASA PADA MAHASISWA PERANTAU DI LINGKUNGAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS MUHAMADIYAH JAKARTA: KAJIAN SOSIOLINGUISTIK - Mariska, Anggi; Kartikasari, Ratna Dewi (Universitas Madura, 2022)
In addition to functioning as a communication tool between people, language can also be used as a tool to identify a person's identity. This article discusses the various language variations that exist at the Faculty of Indonesian Language and Literature Education, Muhammadiyah University, Jakarta. The occurrence of language variations is not only caused by various speakers, but also because of the social interaction activities carried out. The existence of the use of their first language and dialect that affects their language conditions, has resulted in the imperfect use of the Indonesian language among campuses. This study aims to describe language variations and the factors that cause language variations. This research includes field research using qualitative descriptive methods. The research method used is the listening method with observation, recording, and note-taking techniques. The results show that the language used by students varies greatly. The factors that cause language variations are social factors and situational factors. Social factors (environmental) and situational factors (linguistic and kinship situations).